Heterocyclic Aminoboron Compounds as Antituberculosis Agents. Issue 2 (30th January 2014) - Campbell‐Verduyn, Lachlan S.; Bowes, Eric G.; Li, Haoxin; Vallée, Alain M.; Vogels, Christopher M.; Decken, Andreas; Gray, Christopher A.; Westcott, Stephen A.
ABSTRACT We have examined six boron compounds for their potential antituberculosis activities. Addition of 2‐formylphenyl pinacol boronate ester to tetraamine derivatives gave three new aminoboron compounds, which were elementally pure when obtained, and one example was characterized by a single crystal X‐ray diffraction study. Heterocyclic aminoboron compounds 1–4 showed moderate degrees of antimycobacterial activity against Mycobacterium tuberculosis.